2017
DOI: 10.1515/jvetres-2017-0067
|View full text |Cite
|
Sign up to set email alerts
|

MDA and GSH-Px activity in transition dairy cows under seasonal variations and their relationship with reproductive performance

Abstract: IntroductionThe purpose of the current study was to evaluate the blood glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) levels under seasonal variations in dairy cows during transition period, and to assess the relationship between chosen reproductive parameters, GSH-Px, and MDA.Material and MethodsHolstein cows calving in January were assigned into winter group (n = 42), while cows calving in August were assigned into summer group (n = 42). Blood samples were collected from the jugular vein 21, 14, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 39 publications
6
22
0
1
Order By: Relevance
“…The present study results showed low GSH-Px activity in cows with low-BCS during the transition period. Additionally, higher GSH-Px activity, in both groups, was found at prepartum period than after calving, similar to reports by Colakoglu et al (2017) and Festila et al (2012). As in MDA concentrations, the discrepancies in relative GSH-Px activity may be related to sampling time and BCS point used in groups of the studies.…”
Section: Discussionsupporting
confidence: 91%
“…The present study results showed low GSH-Px activity in cows with low-BCS during the transition period. Additionally, higher GSH-Px activity, in both groups, was found at prepartum period than after calving, similar to reports by Colakoglu et al (2017) and Festila et al (2012). As in MDA concentrations, the discrepancies in relative GSH-Px activity may be related to sampling time and BCS point used in groups of the studies.…”
Section: Discussionsupporting
confidence: 91%
“…Malondialdehyde is the final product of lipid peroxidation, a process that occurs as a consequence of oxidative stress [18,38]. Although the values here reported are in the middle of the range of those previously reported for dairy cows during the transition period [39][40][41][42][43], they followed a similar pattern, characterized by a significant increase in the first two weeks after calving. These results suggest that both groups experienced limited degrees of oxidative stress, and cows in the HFM group were increasingly exposed to oxidative damage during the second week postpartum.…”
Section: Discussionsupporting
confidence: 56%
“…[ 14 ] and Colakoglu et al . [ 5 ] concerning MDA concentration measured during early puerperium and late puerperium until mid-lactation. All previous studies agree that significant changes in oxidative stress are observed, especially during the transition period [ 5 , 14 , 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] concerning MDA concentration measured during early puerperium and late puerperium until mid-lactation. All previous studies agree that significant changes in oxidative stress are observed, especially during the transition period [ 5 , 14 , 15 , 17 ]. In fact, increasing the amount of glutamine in the transition period has effective effects on increasing antioxidant capacity and can lead to increased dry matter intake [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation